Kinds of crossed modules - Loma Ahmed Khalel; Abdulalee Jasim Mohammed (College of Education for Pure Sciences, 2009)
Abstract This investigate concerned with some kinds of crossed module like pre cross modules, partially crossed module and crossed squares and it relations with semi-direct products of crossed module.